The angel and the three men - "khan, saniyasnain" (India, Goodword kidz, 2011)
The story narrates the tale of three men who were tested by Allah's blessings. Two of them failed to show gratitude, while the third recognized and appreciated the blessings bestowed upon him. Through this narrative, the book emphasizes the importance of gratitude and recognizing Allah's gifts.